VITAMIN D, CALCIUM, AND PHOSPHORUS STATUS IN CHILDREN WITH SPINA BIFIDA - Boyarchuk, Oksana; Hlushko, Katerina; Dobrovolska, Lesya; Hrekh, Anastasiia; Savuliak, Yaroslav; Vorontsova, Tamara; Volianska, Liubov (Eastern Ukrainian Medical Journal, 2024)
Introduction. Children with spina bifida (SB) are at the highest risk of developing vitamin and mineral deficiencies, including vitamin D, due to a sedentary lifestyle, prolonged indoor stays, and dietary peculiarities. The aim of our study was to determine the dietary intakes of vitamin D, calcium, and phosphorus in children with spina bifida and the concentration of these nutrients in the serum of children with SB. Materials and Methods. The study included 20 children aged 2 to 17 years with congenital neural tube defect (spina bifida). The control group consisted of 67 healthy children aged 6 to 17 years. To determine the dietary intakes of vitamin D, calcium and phosphorus, children or their parents were surveyed using a questionnaire containing questions about the amount of consumption of certain food products over the week. The total amount of vitamin D, calcium, and phosphorus in the weekly diet were calculated, as well as their average daily intakes with food and overall. The concentration of 25-OH vitamin D, calcium, and phosphorus in the blood serum was determined using an enzyme immunoassay. Results. Among the examined children with SB, girls predominated (70.0%). Physical development delay and undernutrition were identified in 3 (15.0%), overweight - in 6 (30.0%) children. Most children with SB exhibited clinical manifestations of mineral metabolism disorders: body proportion disturbances (55.0%), posture disorders (40.0%), scoliosis and/or chest deformity (50.0%), caries (40.0%). Despite the presence of dairy, meat, and fish products in the weekly diet of all children with SB, their quantity was insufficient to meet the daily needs for vitamin D, calcium, and phosphorus. Inadequate intake of vitamin D from food occurred in 70.0% of children, calcium deficiency in 90.0%, phosphorus deficiency in 80.0%, with the alimentary provision of calcium and phosphorus in children with SB being significantly lower than in healthy children (p=0.0027 and p=0.0047, respectively). Optimal levels of vitamin D in the blood serum were observed in only 10.0% of children with SB, which was twice less than in healthy children, while its deficiency was observed 1.5 times more often in children with SB than in healthy children. Half of the patients with SB had reduced calcium levels, and 70.0% had reduced phosphorus levels. Conclusions. The study results demonstrate a wide prevalence of vitamin D deficiency and insufficiency (in 90.0%), calcium and phosphorus deficiency in children with SB, indicating the need for additional intake of these nutrients alongside dietary and lifestyle corrections. Further research on a larger cohort of patients with supplementation regimens is necessary to reduce the risk of complications and improve the quality of life for children with SB.